2006
DOI: 10.1093/ije/dyl041
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the nature of the CRP–coronary event association using Mendelian randomization

Abstract: A common CRP gene polymorphism is associated with important differences in CRP concentrations, free from confounding. The null association of this variant with coronary events suggests possible residual confounding (or reverse causation) in the CRP-coronary event association in observational studies, though the confidence limits are still compatible with a modest causal effect. Additional studies of genotype (or haplotype) and coronary events would help clarify whether or not the link between CRP and coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
129
1
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(138 citation statements)
references
References 69 publications
6
129
1
2
Order By: Relevance
“…The results of the present study suggest that IL-6-mediated inflammatory reactions are potential confounders of the associations of fibrinogen and CRP with risk of CHD. Some reports on the lack of association of functional genotypes for fibrinogen [24] and possibly CRP [25] with risk of CHD are consistent with the hypothesis that the associations of circulating inflammatory markers (including fibrinogen and CRP) with risk of CHD (and mortality) may result from effects of multiple adverse environmental influences [12], some of which may be mediated by IL-6 and other proinflammatory cytokines. However, a significant association between CRP genotypes and cardiovascular events has recently been reported in a large study [26] and further studies of genotypes for inflammatory markers and CVD risk are required.…”
Section: Discussionsupporting
confidence: 57%
“…The results of the present study suggest that IL-6-mediated inflammatory reactions are potential confounders of the associations of fibrinogen and CRP with risk of CHD. Some reports on the lack of association of functional genotypes for fibrinogen [24] and possibly CRP [25] with risk of CHD are consistent with the hypothesis that the associations of circulating inflammatory markers (including fibrinogen and CRP) with risk of CHD (and mortality) may result from effects of multiple adverse environmental influences [12], some of which may be mediated by IL-6 and other proinflammatory cytokines. However, a significant association between CRP genotypes and cardiovascular events has recently been reported in a large study [26] and further studies of genotypes for inflammatory markers and CVD risk are required.…”
Section: Discussionsupporting
confidence: 57%
“…This finding is similar to that reported in the West of Scotland Coronary Prevention Study. 21 Casas et al 4 found that subjects with the variant genotype (TT) of the CRP þ 1444 C/T polymorphism had a higher BMI than the wildtype allele carriers. However, their study was restricted to male Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Polymorphisms in the CRP gene have been associated with anthropometric characteristics (such as BMI) in humans. 4 Interleukin-6 (IL-6) is a pleiotropic cytokine with an important role in both immunoregulation and non-immune events in most cell types and tissues outside of the immune system. 5 IL-6 binds its receptor (IL-6R), and thereby activates an intracellular signaling cascade leading to the inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…But animal studies are not able readily to answer questions about cardiovascular disease. Human studies of organ-specific gene knockouts or upregulation present different obstacles, although the concept of 'Mendelian randomisation' has been used, particularly in cardiovascular risk, to explore the role of several putative mechanisms [71]. Human intervention studies are generally pharmacological.…”
Section: Demonstrating Causation-the Need For Experimentsmentioning
confidence: 99%